PENGARUH PENGALAMAN KERJA, TINGKAT PENDIDIKAN DAN PROFESIONALISME TERHADAP KINERJA KARYAWAN PADA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) BHAKTI SUMEKAR SUMENEP - jurnalmap map; Wahyu Dony Saputra; Chamariyah ÔÇì; Subijanto ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This research was conducted at the Sharia Community Financing Bank (BPRS) Bhakti Sumekar Sumenep. The objectives of this study are: 1). To find out a description of work experience, level of education, professionalism and performance of employees in the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep. 2). To find out and analyze whether work experience, level of education and professionalism simultaneously have a significant influence on the performance of employees in the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep. 3). To find out and analyze whether work experience, level of education and professionalism partially have a significant influence on the performance of employees in the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep. 4). To find out and analyze which variables between work experience, level of education and professionalism that have a dominant influence on employee performance in the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep. Keywords: Work Experience (X1), Level of Education (X2), Professionalism (X3) and Service Quality (Y)